Implications of Matteo Ricci's Missionary Methods for Sinicization of Christianity - YANG, Sitong (Journal of Research for Christianity in China (JRCC), 2023)
Matteo Ricci had a significant impact on the cultural exchanges between China and the West during the Ming and Qing dynasties. His adaptive missionary methods drew the attention of scholars at home and abroad, and was an important part of Sinicization of Christianity. Matteo Ricci not only adhered to the adaptive missionary strategy and gained the support of the literati-official class by changing his Confucian costumes and presenting western things, but also studied and translated Confucian classics in depth, and wrote missionary books in Chinese. Through the collision of Christian thought and Confucianism, he promoted the mutual understanding between China and the West. His missionary experience revealed the importance of respecting and seriously learning to understand different cultures, shedding light on the Chinese Rites Controversy that had lasted for centuries and caused heated debates between East and West, and is still important for cultural exchanges today.
Keywords: Matteo Ricci, Adaptive missionary methods, Sinicization of Christianity, Chinese Rites Controversy